Efeito da abundância de macroalgas sobre a condição corporal de peixes marinhos no rio grande do norte, brasil - Marques, Alexandre de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Macroalgal banks in marine environments may provide shelter and food for fish and other organisms, and may influence the body condition of the individuals present in these environments. Therefore, it is important to understand the action of the abundance of seaweed on the physiological state of fish. Thus, the present study had as objective to evaluate the effect of the abundance of macroalgae on the body condition of marine fish. Thus, bi-lateral bottom trawls were carried out in coastal areas of the municipalities of Baía Formosa and Porto do Mangue on the east and north coast, respectively, of the state of RN. The bottom trawls were performed with the aid of camaroeiro type doors and lasted for 20 minutes each. Subsequently, background water samples were collected for analysis of total phosphorus, total carbon, total nitrogen, dissolved oxygen and salinity, in addition to having been verified in situ at bottom and surface temperature, pH and transparency. Soil sample was collected for analysis of organic matter. The collected biological material was separated, the fish being stored in isothermal boxes with ice and the algae only weighed in each trawl. In the laboratory, the fish were identified and had their standard length and total weight measured. The abundance of algae was an important factor in the variables sampled, and an increase in algal density was verified during the rainy season in both collection sites. Multivariate statistical techniques were used to determine the effect of environmental factors on the condition of 13 fish species. Differences between periods at each site and conditions were evaluated by the statistical package PERMUCO, in software R. Among the 13 species evaluated, six presented a better condition during the period that presented greater abundance of algae. Regardless of the analyzed site, there was better condition for rainy season, when there was also an abundance of macroalgae. In this way, it is concluded that the presence of macroalgae positively influences the body condition for several fish species, providing food and habitats for these species
Keywords: Ictiologia; Fauna Acompanhante; Algas; Ichthyology; Bycatch; Algae; CIENCIAS AGRARIAS::MEDICINA VETERINARIA